Literary text and historical discourse: A questionnaire study - Zhakulayev, Adil; Takirov, Sarzhan; Khassenov, Bolat (International Journal of Innovative Research and Scientific Studies, 2024)
This article explores historical discourse in a literary text from a fresh perspective through an experiment. We compiled the experiment’s questions in a Google Form, drawing inspiration from Askar Altai’s "The Hunchbak." The main emphasis in formulating the questions was placed on the category of historical figures in historical discourse. 23 students of Karaganda Buketov University, aged 19-22, voluntarily took part in our experiment. We chose a descriptive method for data analysis in the study. Using this method, three levels of reader perception (simple, medium, and high) are fully analyzed. As a result of the research, it was found that the vast majority of the survey participants fully understood the text of the literary work, thought about the subtext (indirect meaning) in it, analyzed the text from the point of view of their own knowledge, analyzed the author's position, and tried to express their thoughts. This indicates that the reader’s perceived level of comprehension is moderate. At the same time, the study showed that in the minds of the youth of the postcolonial country there are still some manifestations of ‘colonialism’; it is concluded that for the full recovery of a postcolonial country from ‘colonial diseases’, the full revival of historical consciousness, school programs and textbooks should be revised in Kazakhstan, and colleges and universities should have a systematic, fundamental state program for a long period (25 years).